Psychological determinants of pre-hypertension among students in a pre-university college in Malaysia - Intiaz Hussein, Mohd Hafeez; Md. Said, Salmiah; Muhamad Saliluddin, Suhainizam (Malaysian Medical Association, 2017)
Background: Pre-hypertension is defined as Systolic blood pressure 120-139 mmHg and/or diastolic blood pressure 80-89mmHg. The prevalence of pre-hypertension is highest among age group of 18 to 29 years old. Psychosocial factors such as depression, anxiety and stress have been associated with increased in blood pressure and previous studies more focuses on psychological determinants of hypertension than pre-hypertension. This study aim to determine the association between these psychological factors with pre-hypertension. Materials and Methods: A cross-sectional study was conducted in 2016 among students of a pre-university college in Malaysia. A stratified random sampling by gender was conducted, and a total of 761 students participated in this study with 179 male and 592 female participants. The Malay version of DASS-21 was used to elicit the level of depression, anxiety and stress. Blood pressures were measured twice using sphygmomanometer and the average readings were taken for further data analysis. Binary multiple logistic regression was done to identify factors of prehypertension. Result: The percentage of pre-hypertension was 34.2 % (95%CI [30.1, 38.3]. The percentage of pre-hypertension were higher among those with severe and extremely severe depression (71.4%), severe and extremely severe anxiety (45.6%) and severe and extremely severe stress (51.5%) as compared to those with no depression, anxiety and stress respectively. Severe and extremely severe depression are 5 times more of getting pre-hypertension as compared to those with no depression. Conclusion: The study noted one-third of respondents had pre-hypertension and that only severe and extremely severe depression is associated with pre hypertension. By reducing depression will prevent progression of pre-hypertension to hypertension and other cardiovascular diseases. This can be done through improvement of mental health status and well-being and underline importance for strengthening mental health in the UN Development Agenda 2030 Sustainable Development Goals.